ERYSIPELAS PENIS - Ilko Bakardzhiev; George Pehlivanov (Peytchinski Publishing, 2011)
Erysipelas is an acute streptococcal skin infection. The most common localizations of the disease are the lower extremities, face and trunk. Venous insufficiency, stasis ulcerations, inflammatory dermatitis, dermatophyte infections, insect bites and surgical incisions are the most common points of entry. We present a case report of a 28 year old male with erysipelas penis, combined with non-gonococcal urethritis, treated successfully with Moxifloxacin.